PENERAPAN KEBIJAKAN ELEKTRONIK FAKTUR PAJAK DALAM RANGKA KEMUDAHAN PELAYANAN KEPADA WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK BEKASI SELATAN - Mega Kusuma; Nopikah Safitri (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
Tax is one of the important components of the State administration because of all activities that enter the State treasury. Based on this it becomes very important how the Directorate of Tax Jederal as a state institution in charge of taxation can create policies that can maximize tax revenue for the country. And one of the policies made by the Directorate General of Taxes is an electronic Tax Invoice referred to as an e-invoice which was officially launched on 1 July 2014. The emergence of the policy is based on the abundance of tax invoices in the form of fictitious taxes with a high number of violations.The purpose of this study is to determine the implementation of Electronic Tax Invoice policy in order to ease service to taxpayers at the tax service office pratama South Bekasi.This type of research used in this research is descriptive by using qualitative approach.The results showed that the Application of Electronic Tax Invoice Policy In A Framework of Ease to Taxpayers at the Office Pratama South Bekasi Overall quite good although there are still some that hamper in the manufacture of tax invoices and affect taxpayer compliance such as uneven socialization conducted by the tax service office,Servers are often down / offline,An unstable Internet network, Knowledge of taxable companies that are still less policy-related and the lack of members of the tax authorities to socialize the policy in the Tax Office itself.